Efektivitas Massage Payudara dengan Teknik “Z” Terhadap Produksi ASI Ibu Nifas - Ana Rofika (PROFESSIONAL HEALTH JOURNAL, 2023)
Introduction: A decrease in breast milk production in the first days after giving birth can be caused by a lack of stimulation of the hormones oxytocin and prolactin which play a very important role in the smooth flow of breast milk, causing breast milk not to come out immediately after delivery and the baby having difficulty sucking on the mother's nipple. Currently, in midwifery services, complementary-based services have emerged, which often include breast massage to overcome irregularities in breast milk production. Breast massage is the act of gently massaging the breasts which can be done every day. Method: This study aims to determine the effectiveness of breast massage using the "Z" technique on breast milk production in postpartum mothers. This type of research uses a Quasi-experimental method, the design used is Nonequivalent control group design. This study consisted of 2 (two) groups, namely a control group and a treatment group who were given breast massage using the "Z" technique. The research subjects were 30 postpartum mothers who breastfed their babies. The sampling technique uses purposive sampling. Results: The results of the research were that of the 15 postpartum mothers in the treatment group after breast massage using the "Z" technique, the majority experienced smooth breast milk production, 11 people experienced smooth breast milk production, and 4 postpartum mothers experienced fairly smooth breast milk production. Meanwhile, the 15 postpartum mothers in the control group mostly experienced fairly smooth breast milk production for 9 people, 2 people had breast milk flow smoothly and 4 people had less than smooth breast milk production. It can be concluded based on the results of the hypothesis test showing that the p value < α is 0.000< 0.05 so that breast massage using the "Z" technique is effective on breast milk production in postpartum mothers with an average increase of 144.50 ml. Recommendation: It is hoped that the results of this research will provide input for the health profession in an effort to increase the attainment of exclusive breastfeeding and to overcome the problem of breast milk production during the postpartum period. Keywords: postpartum mothers, breast massage, "Z" technique, breast milk production.